THE ROLE OF ENGLISH USING BUSINESS COMMUNICATION STRATEGIES FOR INTRODUCING MICRO, SMALL AND MEDIUM ENTERPRISES (MSME) IN SOPPENG REGENCY - Mutmainna Herman; Indrawaty Asfah; Asriati (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2025)
The function of English in introducing micro, small, and medium-sized businesses (MSMEs) in Soppeng Regency through business communication techniques. thesis. English Department D4 at Makassar State University's Faculty of Language and Literature. In order to promote the welfare of its citizens, Indonesia, a growing nation, keeps expanding its collaboration with other nations in a number of areas, including commerce and investment. Consumer purchasing power is currently declining as a result of the crisis that is hitting practically every nation. UMKM in Indonesia is one of the groups impacted by the crisis. SMEs need a strategy to survive and compete in this crisis. This strategy not only targets the local scope but also the international one. One of those strategies is mastering English in the business world. English is an international language that serves as a means of communication for people around the world. The ability to communicate in English can be used in various aspects of life. Language skills for business practitioners can be utilized for optimal product development, whether from SMEs or small businesses, such as marketing. The purpose of this research is to understand the role, constraints, and impact of English as the medium of instruction in business or marketing. This research uses descriptive qualitative research. The research subjects are MSME actors in Soppeng, with the research period from June to July 2024. The data collection method uses observation, interviews, and documentation techniques. From the research results, the role of English as a medium of communication in interacting with consumers is very important because it impacts long-term business efforts. Moreover, the challenges faced by MSME actors include difficulties in pronunciation and a lack of vocabulary knowledge. very relevant for SMEs because this approach is designed to meet specific language needs in a business context. By focusing on directly applicable communication skills, it enables MSMEs to understand technical terminology, marketing strategies, and negotiation tactics that are often required in international business interactions.